Covered cloacal extrophy- a diagnostic dilemma - Aziz Ahmad Chattha; Mehboob Ahmad; Muhammad Abdullah; Muhammad Saleem; Imran Hashim; Zubair Shoukat (Elsevier, 2021)
Background: Covered cloacal extrophy (CCE) is extremely rare condition. It requires a high index of suspicion for its diagnosis. External features are quite similar to that of common cloaca i.e. intact lower abdominal wall and single perineal opening whereas visceral features are similar to cloacal extrophy (CE). Case presentation: 3 day old female neonate presented to the emergency department with single perineal opening and stool coming out of umbilicus as well as perineal opening. Abdominal wall was intact. After detailed workup, she underwent exploratory laparotomy and was diagnosed as covered cloacal extrophy. Conclusion: Wide spectrum of cloacal malformation makes covered cloacal extrophy a diagnostic challenge and early diagnosis is helpful in strategizing future reconstructions.